Konsep Pendidikan Akhlak Menurut Ibnu Qayyim Al-Jauziyah: Studi Literatur Perspektif Pendidikan Islam - YM, Khairuddin; Syahputri, Leli; Halimah, Halimah; Hasanah, Nurul; Mahmuda, Muhammad; pengelola, pengelola (TABYIN: JURNAL PENDIDIKAN ISLAM, 2024)
This study aims to examine Ibn Qayyim Al-Jauziyah's thoughts on moral education from an Islamic perspective and its relevance to character building in children from an early age. This study employs a literature review method, where the researcher collects, reads, and analyzes various written sources such as books, journals, and scientific articles related to Ibn Qayyim's ideas on moral character development. The findings reveal that moral education, according to Ibn Qayyim, is not merely the teaching of moral theories but an ongoing process involving modeling, habit formation, and consistent guidance. Moral education must begin in the family, be reinforced in school, and be maintained in the community. He divides moral education into two main aspects: education of the heart and education of actions, which are interrelated in shaping a person's character. Values such as honesty, patience, responsibility, humility, respect for teachers and parents, and guarding one's speech are the main focus of the educational process according to Ibn Qayyim. This article recommends that parents, teachers, and educational institutions adopt this concept as a guide for effectively and sustainably instilling moral values.